2004
DOI: 10.1556/avet.52.2004.2.4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the prevalence of infectious bronchitis virus type 4/91 in Iran

Abstract: To evaluate the prevalence of infectious bronchitis virus (IBV) type 4/91 in Iran, tracheal swabs from 77 broiler flocks in 16 provinces were collected at the slaughterhouse. Swabs were subjected to RNA extraction and tested by RT-PCR, followed by a type-specific nested PCR. The viral RNA was detected in 33 samples (42.8%) from different provinces. The results indicate a relatively high prevalence of IBV type 4/91 in Iran and necessitate revising the vaccination programme against this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…The first isolation of IBV in Iranian flocks was reported in 1994. Currently, Ma5, H120, and attenuated 4/91 IBV-based vaccination strategies have been applied for IB control in poultry farms in Iran (Seyfi Abad Shapouri et al, 2004;Hashemzadeh et al, 2013). However, there have been frequent reports of IB-suspected cases from all over the country because of the immune failure.…”
Section: Discussionmentioning
confidence: 99%
“…The first isolation of IBV in Iranian flocks was reported in 1994. Currently, Ma5, H120, and attenuated 4/91 IBV-based vaccination strategies have been applied for IB control in poultry farms in Iran (Seyfi Abad Shapouri et al, 2004;Hashemzadeh et al, 2013). However, there have been frequent reports of IB-suspected cases from all over the country because of the immune failure.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the major poultry pathogens and causes heavy economic losses. Currently, Ma5, H120, and attenuated 4/91 IBV-based vaccination strategies have been applied for IB control in poultry farms in Iran (11,12). In our study, the prevalence rate was 37.5% and Variant-2 like being the dominant genotype in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was first identified in France in 1985 and subsequently identified in Great Britain in 1990, this genotype has spread to many countries and become one of the most predominant types in Europe [2,6,7]. This IBV genotype has also been detected in Middle Eastern and Asian countries, such as Iran and Thailand [6,16]. However, this genotype was not found in our previous report using isolates from up to mid-2003 [14], in which we reported that the recent IBV isolates in Japan could be classified into three major genotypes (JP-I, JP-II and JP-III).…”
mentioning
confidence: 98%